Transient receptor potential canonical-3 channel-dependent fibroblast regulation in atrial fibrillation - Harada, Masahide; Voigt, Niels; Dobrev, Dobromir (Circulation, 2012)
Background—Fibroblast proliferation and differentiation are central in atrial fibrillation (AF)-promoting remodeling. Here, we investigated fibroblast regulation by Ca2ϩ-permeable transient receptor potential canonical-3 (TRPC3) channels. Methods and Results—Freshly isolated rat cardiac fibroblasts abundantly expressed TRPC3 and had appreciable nonselective cation currents (INSC) sensitive to a selective TPRC3 channel blocker, pyrazole-3 (3 ␮mol/L). Pyrazole-3 suppressed angiotensin II-induced Ca2ϩ influx, proliferation, and ␣-smooth muscle actin protein expression in fibroblasts. Ca2ϩ removal and TRPC3 blockade suppressed extracellular signal-regulated kinase phosphorylation, and extracellular signal-regulated kinase phosphorylation inhibition reduced fibroblast proliferation. TRPC3 expression was upregulated in atria from AF patients, goats with electrically maintained AF, and dogs with tachypacing-induced heart failure. TRPC3 knockdown (based on short hairpin RNA [shRNA]) decreased canine atrial fibroblast proliferation. In left atrial fibroblasts freshly isolated from dogs kept in AF for 1 week by atrial tachypacing, TRPC3 protein expression, currents, extracellular signal-regulated kinase phosphorylation, and extracellular matrix gene expression were all significantly increased. In cultured left atrial fibroblasts from AF dogs, proliferation rates, ␣-smooth muscle actin expression, and extracellular signal-regulated kinase phosphorylation were increased and were suppressed by pyrazole-3. MicroRNA-26 was downregulated in canine AF atria; experimental microRNA-26 knockdown reproduced AF-induced TRPC3 upregulation and fibroblast activation. MicroRNA-26 has NFAT (nuclear factor of activated T cells) binding sites in the 5Ј promoter region. NFAT activation increased in AF fibroblasts, and NFAT negatively regulated microRNA-26 transcription. In vivo pyrazole-3 administration suppressed AF while decreasing fibroblast proliferation and extracellular matrix gene expression. Conclusions—TRPC3 channels regulate cardiac fibroblast proliferation and differentiation, likely by controlling the Ca2ϩ influx that activates extracellular signal-regulated kinase signaling. AF increases TRPC3 channel expression by causing NFAT-mediated downregulation of microRNA-26 and causes TRPC3-dependent enhancement of fibroblast proliferation and differentiation. In vivo, TRPC3 blockade prevents AF substrate development in a dog model of electrically maintained AF. TRPC3 likely plays an important role in AF by promoting fibroblast pathophysiology and is a novel potential therapeutic target. (Circulation. 2012;126:2051-2064.)
Gesehen am 06.08.2018